Biofiltration of acetaldehyde resulting from ethanol manufacturing facilities. (February 2020) - Duerschner, Chris; Hassan, Ashraf Aly; Dvorak, Bruce
Abstract: At ethanol plants, the control of acetaldehyde emissions is accomplished by scrubbers and regenerative thermal oxidizers. However, their operation imposes substantial operating costs. Alternatively, two biotrickling filters were operated in parallel under acetaldehyde loadings ranging from 4 to 136 g m −3 hr −1 . One filter was operated at room temperature while the other one was heated to 60 °C, to mimic hot drier emissions. The unheated filter maintained 100% removal efficiency up to 45.28 g m −3 hr −1 loading rate at 30-s empty bed residence time. Highest elimination capacity recorded was 112 g m −3 hr −1 at 83.2% removal efficiency. The heated filter achieved removal efficiency larger than 60% at influent concentrations of 200 ppmv and lower, however, removal was significantly lower at 400 and 600 ppmv influent concentrations. Performance was improved by reseeding with cooking compost resulting in increased thermophilic bacterial population. Main byproduct formed was acetic acid with traces of formic acid. Mathematical modelling was used to successfully describe acetaldehyde concentration profiles. Graphical abstract: Image 1 Highlights: High thermophilic acetaldehyde removal was achieved at low loading rates. Thermophilic removal suffered significantly at higher influent concentrations. At room temperature, a maximum elimination capacity of 112 g m −3 hr −1 is achieved. The main biodegradation byproduct of acetaldehyde is acetic acid.